2022
DOI: 10.1257/app.20200405
|View full text |Cite
|
Sign up to set email alerts
|

The Roots of Health Inequality and the Value of Intrafamily Expertise

Abstract: In the context of Sweden, we show that having a doctor in the family raises preventive health investments throughout the life cycle, improves physical health, and prolongs life. Two quasi-experimental research designs—medical school admission lotteries and variation in the timing of medical degrees—support a causal interpretation of these effects. A hypothetical policy that would bring the same health behavior changes and benefits to all Swedes would close 18 percent of the mortality-income gradient. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 89 publications
2
15
0
Order By: Relevance
“…Our findings are also specific to a particular period in the history of a particular infectious disease. Nonetheless, they complement a growing literature that emphasizes the importance of non-medical factors in driving health inequality (e.g., Fuchs 1974;Case and Deaton 2015;Chetty et al 2016;Finkelstein et al 2021;Chen, Persson, et al 2022).…”
Section: Introductionmentioning
confidence: 65%
“…Our findings are also specific to a particular period in the history of a particular infectious disease. Nonetheless, they complement a growing literature that emphasizes the importance of non-medical factors in driving health inequality (e.g., Fuchs 1974;Case and Deaton 2015;Chetty et al 2016;Finkelstein et al 2021;Chen, Persson, et al 2022).…”
Section: Introductionmentioning
confidence: 65%
“…5,6,[18][19][20][21][22] Qualitatively, the results among children and adolescents who were all enrolled in Medicaid (at least at the time of measurement) were consistent with findings in non-US high-income contexts that children in lower-income families have worse health even in the presence of health insurance. [22][23][24][25][26][27][28][29] For the US context, unlike the study by Evans et al 7 but similar to the study by Case et al 5 and other studies, injuries and a diagnosis of asthma were significantly associated with family income. [30][31][32] There was no statistically significant association between family income and 10-year mortality among children aged 5 to 9 years, which is in contrast to many studies that have found that an income-mortality gradient is present at any age.…”
Section: Discussionmentioning
confidence: 86%
“…Drawing on admission lottery data that links children's field of education to relatives' health outcomes, two quasiexperimental studies come to opposite conclusions. Chen et al (2022), using Swedish data, find important health benefits to having a physician in the family, Artmann et al (2022) however find no such causal effect in the Netherlands.…”
Section: Causal Pathways and Current Evidencementioning
confidence: 98%